PENGARUH BUDGETARY SLACK TERHADAP KINERJA SKPD DENGAN KOMITMEN ORGANISASI DAN KAPASITAS INDIVIDU SEBAGAI VARIABEL MODERASI - Mohammad Arfandi Adnan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study aims to examine and analyze the relationship budgetary slack on performance SKPD with the organization's commitment and capacity of the individual as a moderating variable on SKPD Polewali Mandar West Sulawesi Province. This study uses a quantitative approach with a cross section observation.The research data was obtained through a questionnaire of 120 eksamplar the structural official eselon III and IV at SKPD. Of the 120 eksamplar returned and declared valid as much as 110 respondents. Data were analyzed using SPSS program factor analysis with 21. The results showed that Budgetary slack significant negative effect on the performance of SKPD. Budgetary slack negative and significant effect on organizational commitment. Organizational commitment and significant positive effect on the performance of SKPD. Budgetary slack on performance on education through organizational commitment positively and significantly affect and individual capacities can’t moderate influence on the performance of SKPD Budgetary slack.